Estrategia metodológica para mejorar el desarrollo de destrezas del drible, pases y lanzamientos del baloncesto en los estudiantes del 8avo. año de educación básica, área de educación física del colegio Técnico Agropecuario Tcnel. Lauro Guerrero, de Lauro Guerrero, cantón Paltas, provincia de Loja, período 2012– 2013 - Songor Córdova, Miguel Stalin (2015)
Having as base the Ecuadorian State, - what access to physical education, sport and recreation is a right that assists all citizens--the idea of researching and finding the solution to the problem of ¿how to improve the development of the skills of the dribble, pass and shoots the basketball in the students of 8th year of basic General Education College agricultural technical "Tcnel. do Lauro Guerrero"?, for which arose as a general objective, which consisted of: Design a methodological strategy to improve the development of the skills of dribbling, passing and shooting basketball students in 8th. Year Basic, physical education area of Agricultural Technical School Tcnel. Lauro Guerrero of Lauro Guerrero, Paltas canton, province of Loja. The research replied to a Design and experimental diagnostics. Scientific, historical and logical, analytic-synthetic, inductive-deductive, descriptive, statistical, modeling, Empirical Methods: observation, survey and document analysis to develop this paper the methods used. The most relevant finding that was evident in the diagnosis is, the lack of knowledge of the technical groundwork and the use of methods and procedures applied in the eighth year of basic education students, do not produce improvements in the development of the skills of the dribble, pass and shoots the basketball